Food Quality Profile of Pounded Yam and Implications For Yam Breeding - Otegbayo, Bolanle; Oroniran, Oluyinka; AKISSOE, H. NOËL (My University, 2023)
BACKGROUND: Assessment of the key preferred quality traits in pounded yam, a popularly consumed yam food product in West Africa, is often done through sensory evaluation. Such assessment is time-consuming and results may be biased. Therefore, there is a need to develop objective, high-throughput methods to predict the quality of consumer-preferred traits in pounded yam. This study focused on how key quality traits in pounded yam proposed to yam breeders were determined, measured by biophysical and biochemical methods, in order to shorten the breeding selection cycle through adoption of these methods by breeders. RESULTS: Consumer tests and sensory quantitative descriptive analysis (QDA) validated that preferred priority quality traits in pounded yam were related to textural quality (smooth, stretchable, moldable, slightly sticky and moderately hard) and color (white, cream or light yellow). There were significant correlations between sensory textural quality attributes cohesiveness/moldability, hardness, and adhe- siveness/stickiness, with textural quality measurements from instrumental texture profile analysis (TPA). Color measurement parame- ters (L*, a*, and b*) with chromameter agreed with that of sensory evaluation and can replace the sensory panel approach. The smoothness (R2 = 1.00), stickiness (R2 = 1.00), stretchability (R2 = 1.00), hardness (R2 = 0.99), and moldability (R2 = 0.53) of pounded yam samples can be predicted by the starch, amylose, and protein contents of yam tubers estimated by near-infrared spectroscopy. CONCLUSION: TPA and Hunter colorimeter can be used as medium-high throughput methods to evaluate the textural quality and color of pounded yam in place of the sensory panelists.
Keywords: pounded yam; color; textural quality; texture profile analysis; chromameter; consumer preferences